An Expanded Trial of Scrambler Therapy in the Treatment of Cancer Pain Syndromes And Chronic Chemotherapy-Induced Peripheral Neuropathy - Coyne, Patrick J (J Pain Palliat Care Pharmacother, 2013)
BACKGROUND: Neuropathic pain is common among cancer patients and often difficult to treat. This study used Scrambler Therapy, a patient specific electrocutaneous nerve stimulation device, to treat cancer patient with pain. METHODS: Patients received Scrambler Therapy for ten sessions (one daily) over a two- week period. The primary outcome was change in pain numeric rating scale (NRS) at 1 month; secondary outcomes were changes in the Brief Pain Inventory and European Organization for Treatment and Cancer QLC-CIPN-20 over time. RESULTS: 39 patients, mean age 56.5, 16 men and 23 women, were treated over an 18 month period for an average of 9.3 days each. The “now” pain scores reduced from 6.6 before treatment to 4.5 at 14 days, 4.6, 4.8 and 4.6 at 1, 2 and 3 months. (p<0.001) Clinically important and statistically significant improvements were seen in average, least, and worst pain; BPI interference with life scores, and motor and sensory scales on the EORTC CIPN-20. No adverse effects were observed. CONCLUSIONS: In this single arm trial, Scrambler therapy appeared to relieve cancer associated chronic neuropathic pain both acutely and chronically, and provided sustained improvements in many indicators of quality of life.